2021
DOI: 10.3390/s21217096
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors for Measurement of Viewing Behavior, Light Exposure, and Sleep

Abstract: The purpose of this study was to compare two wearable sensors to each other and to a questionnaire in an adult population. For one week, participants aged 29.2 ± 5.5 years (n = 25) simultaneously wore a Clouclip, a spectacle-mounted device that records viewing distance and illuminance, and an Actiwatch, a wrist-worn device that measures illuminance and activity. Participants maintained a daily log of activities and completed an activity questionnaire. Objective measures of time outdoors, near (10–< 60 cm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Viewing distance was measured objectively using a Clouclip (http://clouclip.com). This was mounted on the right temple of the participant's habitual spectacle frame or a frame provided with plano lenses 34 . The Clouclip is a lightweight Bluetooth spectacle‐mounted device that measures viewing distance every 5 s using infrared time‐of‐flight technology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewing distance was measured objectively using a Clouclip (http://clouclip.com). This was mounted on the right temple of the participant's habitual spectacle frame or a frame provided with plano lenses 34 . The Clouclip is a lightweight Bluetooth spectacle‐mounted device that measures viewing distance every 5 s using infrared time‐of‐flight technology.…”
Section: Methodsmentioning
confidence: 99%
“…This was mounted on the right temple of the participant's habitual spectacle frame or a frame provided with plano lenses. 34 The Clouclip is a lightweight Bluetooth spectacle-mounted device that measures viewing distance every 5 s using infrared time-of-flight technology. The tracking beam diameter is 25° and is angled 10° inferiorly and has been validated for distances of 10-99 cm.…”
Section: Objective Measurementmentioning
confidence: 99%
“…Systematic in-laboratory comparisons of the optical performance of light-logging sensors show large differences in their ability to capture biologically relevant light in commonly used sensors. 25,[34][35][36][37][38][39][40] A recent comprehensive review on light-dosimetry studies showed that in the published literature, there is a large variability of parameters used in these studies. 20 The authors found a total of 25 unique device types used in the literature.…”
Section: Light Exposure Needs To Be Measured In a Personalized Fashionmentioning
confidence: 99%
“…Systematic in-laboratory comparisons of the optical performance of light-logging sensors show large differences in their ability to capture biologically relevant light in commonly used sensors. 25 , 34 40 …”
Section: Introductionmentioning
confidence: 99%
“… 13 Current wearable devices estimating near-work in real-life settings using single time-of-flight sensors have found a mismatch between objective and subjective reports on near-work. 14 , 15 However, single time-of-flight sensors only measure object distances at a limited range and within a narrow field angle (much smaller than the field of fixations). These time-of-flight sensors also introduce inaccuracy at best and systematic biases at worst because they do not take into account the direction of gaze.…”
Section: Introductionmentioning
confidence: 99%